A história da matemática e sua importância no ensino fundamental II: uma reflexão teórica - GUIMARÃES, Wesley Vieira (2022)
The study in question was motivated by the question: In what terms can the history of mathematics contribute to the teaching and learning of mathematical content and concepts in elementary school II? The objective was to know how History of Mathematics can be used as a tool to help the teaching and learning of mathematical content and concepts in Elementary School II, a period that includes the levels from 6th to 9th grade. Thus, this work was developed from a qualitative study of bibliographic character from the perspective of a reflection on the importance of the History of Mathematics in the teaching and learning process. This study was based on references such as D'Ambrósio (1996); Brazil (1998); Bayer (2012); Mol (2013), among others dealing with history, paradigmatic changes, curricular adaptations, and meaning of mathematics in life in society. It was understood that when the history of mathematics is studied in its essence there can be a better understanding of the content and mathematical concepts. At the end of this study the relevance that the use of the History of Mathematics has in both teaching and learning of Mathematics was highlighted. It is hoped that with the changes in human thinking, students will be motivated to learn the subject of calculations, but also that teachers should be touched to reflect their practices and discover the practicality and efficiency that this tool has in Time to teach.